Validation of the short version of the dimensional inventory for child development assessment - Euclides José de Mendonça Filho; Mônia Aparecida da Silva; Natalie A. Koziol; Denise Ruschel Bandeira (Elsevier, 2021)
Objectives: There is a critical need to monitor the development of children around the world, and in Brazil, this need is substantial since there is a paucity of assessment tools. This study aimed to describe the design and provide evidence of reliability and validity for the short version of the Dimensional Inventory for Child Development Assessment (IDADI-short). Methods: A sample of 1,865 biological mothers of children aged 4-72 months (M = 34.8, SD = 20.20) completed the IDADI to assess Cognitive, socio-emotional, Expressive, and Receptive Language and Communication, Fine and Gross Motor, and Adaptive Behavior development. The psychometric properties of a total of 118 subscales of IDADI were obtained and the IDADI-short age-specific scores were correlated with the original inventory, and criteria variables such as neurodevelopment diagnosis, socioeconomic status, and sex. Results: Item Response Theory analysis, Cronbach's Alpha, and McDonald's Omega indicated excellent internal consistency and optimal participant discrimination after minor alterations. IDADI-short scores were strongly associated with the original inventory, with high sensibility and specificity precision for developmental delays. Significant associations with relevant criteria variables were also observed. Conclusion: Findings support the use of IDADI-short as a parental measure of young children's development.